2018
DOI: 10.1016/j.psyneuen.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol and work stress: Importance of workload and stress model (JDCS or ERI)

Abstract: Hair cortisol concentrations (HCCs) are a potential physiological indicator of work related stress. However, studies that tested the relationship between HCC and self-reported stress in a work setting show mixed findings. This may be because few studies used worker samples that experience prolonged stress. Therefore, we compared a high workload sample (n = 81) and a normal workload sample (n = 91) and studied whether HCC was related to: (i) high job demands, low control, and low social support (JDCS model), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 57 publications
2
37
1
1
Order By: Relevance
“… 8 The patterns of worrying and thinking about these stressful situations pervade individuals’ lives, which could result in cumulative burdens that impair the regulatory capacities of the HPA axis. 39 , 40 Moreover, some, 41 43 but not all, 12 , 13 investigators have reported that there is no relationship between work stress and hair cortisol level. However, a significantly higher hair cortisol level was found in workers with symptoms of depression compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 The patterns of worrying and thinking about these stressful situations pervade individuals’ lives, which could result in cumulative burdens that impair the regulatory capacities of the HPA axis. 39 , 40 Moreover, some, 41 43 but not all, 12 , 13 investigators have reported that there is no relationship between work stress and hair cortisol level. However, a significantly higher hair cortisol level was found in workers with symptoms of depression compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“… 44 These findings imply that a certain stress threshold should be reached to detect a significant relationship between self-reported stress and cortisol level. 13 In general, symptoms of depression and burnout are considered to be the psychological outcomes of long-term work stress in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERI questionnaire consisted of three sections: effort ( E , 6 items), reward ( R , 11 items), and overcommitment (6 items), totaling 23 items. Each item was assigned a score ranging from 1 (highly disagree) to 5 (highly agree) [ 20 ] and was attributed the same weight. The index of an effort-reward ratio was ERI = E /( R ∗ C ), where C was the ratio of the number of items of E to the number of items of R .…”
Section: Methodsmentioning
confidence: 99%
“…Job stress refers to people's response under physiological and psychological pressure caused by the imbalance between occupational needs and individual resources, needs, abilities, and knowledge [20]. With the development of society and the increase in life pressure, people bear more and more pressure from society, work, and life.…”
Section: Introductionmentioning
confidence: 99%